Child Maltreatment Investigations in Canada: Main and Moderating Effects of Primary Caregiver Cognitive Impairment. (February 2021) - McConnell, David; Aunos, Marjorie; Pacheco, Laura; Feldman, Maurice
Children of parents with cognitive impairment are overrepresented in the child protection system (CPS). The aim of this study was to examine the relationship between primary caregiver cognitive impairment (CCI) and CPS investigation outcomes using the Canadian Incidence Study of Reported Child Abuse and Neglect (CIS-2008). The CIS-2008 includes process and outcomes data on a national sample of CPS investigations involving a total of 15, 980 children under the age of 16 years. This secondary data analysis found that primary CCI was noted in 6.3% of all investigations. When primary CCI was noted, investigations were 3–4 times more likely to result in child removal and court action. The results further suggest that some case characteristics, including case history variables, are weighted differently in decision making depending on whether or not primary CCI is indicated. A systematic, national strategy is needed to build capacity in government and community sectors for the provision of research-informed child and youth protection and family support services for these parents and their children.